Answer:
We conclude that the two ordered pairs (0, 0) and (-2, 2) are the solutions of the equation y = 2x² + 3x.
Step-by-step explanation:
Given the expression
y = 2x² + 3x
Substituting x = 0
y = 2(0)² + 3(0)
y = 0+0
y = 0
Thus, the ordered pair is: (0, 0)
Now, substituting x = -2
y = 2x² + 3x
y = 2(-2)² + 3(-2)
y = 8 - 6
y = 2
Thus, the ordered pair is: (-2, 2)
Therefore, we conclude that the two ordered pairs (0, 0) and (-2, 2) are the solutions of the equation y = 2x² + 3x.
Answer:
∠ YZX ≈ 19.7°
Step-by-step explanation:
using the sine ratio in the right triangle.
sin YZX =
=
=
, then
∠ YZX =
(
) ≈ 19.7° ( to 3 significant figures )
Answer:
2y-8
-Step-by-step explanation:
2y +4y = 2y
so
2y - 8
Change everything into 10ths as follows:
1/10 + 2.5/10 = 3.5/10 of an hour to make one bracelet. Then change to 20ths so the numerator is a whole number.
Divide your time available by the time it takes to make one.
21
4 = 420= 15 bracelets
7 28
20
(as a whole number there was no fraction or remainder to round off)
Answer:
y = 2x −5
Step-by-step explanation:
The slope is 2 and the Y intercept is -5 so the equation is:
y = 2x -5